Establishment of sampling techniques in papaya using the rapid nitrate test - Tantung, R. L.; Angeles, D. E.; Constantino, M. H. (1996)
Using the rapid nitrate test, sampling techniques in papaya were established. The recently mature leaves gave the highest nitrate concentration when sampled at 9:30 AM. Petiole sap NO-N concentration was higher at the vegetative stage (4 1/2 mos old) compared to reproductive stage (6 1/2 mos old).
Keywords: Papaya -- Planting